Empirical Study of an Air-to-Air Heat Pipe Heat Exchanger in Tropical Climates - Yau, Yat Huang; Ahmadzadehtalatapeh, Mohammad (Taylor & Francis, 2011)
This article presents the empirical study of a heat pipe heat exchanger that was directly experiencing the ambient tropical air in its evaporator section. The performance of the heat pipe heat exchanger was monitored during two weeks of operation to determine the performance curves. The temperature of return air was controlled at about 22°C as the representative temperature of inside air, and a face velocity of 2 m/s on the heat pipe heat exchanger coil was established for this purpose. It was found that for the present investigation, the heat pipe heat exchanger can pay for itself in 1.5 years. Copyright © Taylor & Francis Group, LLC.